931 Implementing safety culture in teacher education - Lindfors, Eila; Somerkoski, Brita (Child and Adolescent Safety, 2016)
BackgroundDuring the past few years the incidents of extreme violence and the increase of unintentional injuries and accidents have created situations where new safety procedures are needed. Safe learning environment should be a safe working environment for teachers. According to the target programs and visions, safety and wellbeing can be seen as basic values of the society.ObjectiveThe New National core Curriculum contains broad-based competence issues such as “Looking after oneself, managing daily activities and safety”. The renewed curricula also includes practical safety issues such as knowing the basic safety signs and symbols, conducting appropriate behaviour in traffic and avoiding dangerous situations. The renewed curriculum sets new challenges also for teacher education. There is a need for new teacher´s safety competence with knowledge and attitude but also the practical skills.ResultsThe curricula for the University of Turku, teacher education in Rauma unit were renewed. The new teacher education curricula include safety and security issues such as safety competence and school subject didactical safety as well as safety in practical training. As a part of their studies the prospective teachers participate to educational lessons or debates, safety walks, fire-drills and monitoring of unintentional injuries. This is preparing the teachers to act safely when working at the school.In addition The Developing Network of Safety in Schools (OPTUKE) has been established. The aim was to advance a wide, systematic and open safety culture in schools as well as to support the process of making safety culture more visible with the help of a pedagogic point of view on safety.ConclusionsThese measures strengthen prospective teachers´safety competence, resilience and ability to respond in the emergency situations